Intensive oral prophylaxis does not alter the tongue microbiome in young patients with chronic kidney disease: longitudinal, randomized, controlled study - Hoefer, Karolin C.; Weber, Lutz T.; Barbe, Anna Greta; Graf, Isabelle; Thom, Stefanie; Ehren, Rasmus; Nowag, Angela; Wisplinghoff, Hilmar; Noack, Michael J.; Scholz, Claus J.; Jazmati, Nathalie (Frontiers in Immunology, 2024)
Introduction: Gingivitis is a common intraoral disease in patients with chronic kidney disease (CKD), which poses a particular interdisciplinary challenge. We aimed to determine the influence of an intensive oral prophylaxis program (OPP) compared to standard prevention measures on the tongue microbiome of young patients with CKD. Methods: Thirty patients with CKD (mean age 14.2±5.2 years) and generalized gingivitis were included. The effects of the intensive OPP were compared with standard prophylaxis according to statutory health insurance (treatment as usual, TAU) as a control. Tongue swabs were taken from the patients at baseline (t1) and after 3 (t2) and 6 (t3) months. Nextgeneration sequencing of 16S rDNA genes was used to quantitatively characterize microbial communities. Results: There were no differences in the abundance, richness, or diversity of the observed genera and species between the two study groups at baseline or after 3 or 6 months. Furthermore, no change in predefined gingivitis and oral health bacterial clusters were found. At the phylum level, Firmicutes were decreased after intervention in the TAU group (t2TAU 42.9±7.1 to t3TAU 34.8±4.7 (npairs=14), p=0.003; false discovery rate 0.02). The decrease of Firmicutes was not significant in the OPP group. Conclusions: Despite the intensity of dental prophylaxis and decreasing clinical signs of inflammation and decreasing plaque amount, no clinically relevant changes in the tongue microbiome were observed. Our results confirm the conserved and stable nature of the tongue microbiome, even in children with CKD.